Successful Treatment with Percutaneous Catheter Drainage and Irrigation for Methycillin-Resistant Staphylococcus aureus Graft Infection Following Abdominal Aneurysm Repair - Taniguchi, Kenichiro; Umesue, Masayoshi; Nakamura, Kenichi; Nagano, Ichiro; Fukumura, Fumio; Boku, Noriko; Ando, Hiromi; Tanaka, Jiro; Kimura, Satoshi (Japanese Journal of Cardiovascular Surgery, 2003)
We report 2 cases of successful treatment by percutaneous catheter drainage and irrigation for methycillin-resistant Staphylococcus aureus (MRSA) prosthetic graft infection after abdominal aortic aneurysm (AAA) repair. Case 1 was a 71-year-old man in whom MRSA graft infection was diagnosed on the basis of high fever and CT-guided taps of the perigraft fluid 11 days after AAA repair, and a percutaneous catheter was inserted into the perigraft space by the CT-guided method. Case 2 was a 77-year-old man in whom MRSA graft infection was diagnosed because of high fever and purulent discharge from the wound of retroperitoneal drainage 5 days after AAA repair. A percutaneous catheter was placed into the retroperitoneal space via an extraperitoneal route. In both cases, intermittent irrigation by 0.5% Povidone-iodine solution and saline was performed as well as systemic and local antibiotic administration. The graft infection was well controlled and both patients were discharged after 4 months. Percutaneous catheter drainage and irrigation can be one of the choices for critically ill patients with graft infection after AAA repair.